Analysis of Sand Dune Encroachment Dynamics and Prediction of Their Evolution in the Benghazi Plain during the Period (2000–2035) (Journal of Libya for geographical studies, 2026)
This study aims to analyze the dynamics of sand dune encroachment in the Benghazi Plain during the period 2000–2025, relying on Landsat and Sentinel-2 satellite imagery, Geographic Information Systems (GIS) techniques, panel data modeling using EViews, and field observations. A spatial analytical approach was adopted to monitor dune distribution, measure their spatial expansion, and analyze annual migration rates. In addition, a descriptive statistical approach was employed to estimate the relationships between climatic and environmental variables and dune movement rates. The results indicate an increase in the dune migration rate from 8.5 to 10.6 m/year, accompanied by a rise in sandy soil proportion from 60% to 64%, while slope remained constant at 1.8 degrees, highlighting the role of geomorphological characteristics in accelerating dune movement. Moreover, the area of active dunes expanded from 160 to 230 km² due to vegetation cover degradation and climatic factors. Projections for the period 2025–2035 suggest a continued increase in migration rates, reaching approximately 13.6 m/year, alongside a decline in the Soil Moisture Index (SMI) from 0.28 to 0.18, reflecting reduced moisture availability, intensified desertification processes, and further degradation of vegetation cover. Consequently, the area affected by sand dunes is expected to reach nearly 300 km². Accordingly, the study recommends the implementation of sustainable desertification control strategies, including land rehabilitation, planting drought-resistant vegetation, and soil stabilization measures. It also emphasizes the importance of adopting integrated dune management and continuous environmental monitoring using satellite imagery and GIS, as well as developing risk indicators such as the Desertification Severity Index (DSI) to support environmental planning and mitigate the impacts of desertification in the region.
Keywords: Sand dune encroachment; Soil Moisture Index (SMI); panel data model; vegetation cover degradation; Benghazi Plain